2014
DOI: 10.4028/www.scientific.net/amr.955-959.208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biogas Slurry Pretreatment on Germination and Seedling Growth of <i>Vicia faba</i> L.

Abstract: In order to study the effect of seed soaking with biogas slurry on seed germination and growth of faba beans (Vicia faba L.), the experiment was conducted. The seeds were soaked in biogas slurry for various soaking durations (0, 2, 4, 6 and 8 hours) and different concentration (0, 25, 50, 75 and 100 %) along with control to determine the optimal soaking duration and find out the best growing condition. The highest germination rate, germination potential and germination index were obtained when the faba beans s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“… Seeds of Vicia faba (L.) soaked in 75% BGS for 4 h showed the highest germination potential, germination rate, and germination index. Zhao et al [ 65 ] BGS at different concentrations (1:1, 1:2, and 1:4) Promotes plant growth, nutrient levels, and water-use efficiency. Promotes growth (root length, plant height, root and shoot biomass, etc.)…”
Section: Bgs: Source Composition and Agricultural Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“… Seeds of Vicia faba (L.) soaked in 75% BGS for 4 h showed the highest germination potential, germination rate, and germination index. Zhao et al [ 65 ] BGS at different concentrations (1:1, 1:2, and 1:4) Promotes plant growth, nutrient levels, and water-use efficiency. Promotes growth (root length, plant height, root and shoot biomass, etc.)…”
Section: Bgs: Source Composition and Agricultural Applicationsmentioning
confidence: 99%
“…Garg et al [ 64 ] recovered the higher maize grain yields (6.21 Mg ha −1 ) and improvement in root length density (1.10 cm cm −3 ) with the treatment of BGS (at 15 Mg ha −1 ). Zhao et al [ 65 ] in laboratory investigations recorded the highest germination potential, germination rate, and germination index in Vicia faba (L.) seeds soaked in 75% BGS (w/v in distilled water). Du et al [ 66 ] worked on Hoggery BGS and observed a substantial increase in wheat (23.47%) and maize (15.46%) yields.…”
Section: Bgs: Source Composition and Agricultural Applicationsmentioning
confidence: 99%
“…Digestate, for example, can be used for soaking seeds (e.g., faba beans), having a positive effect on seed germination and seedling growth (Zhao et al, 2014). A study of Kupper et al (2006), furthermore, showed that the digestate can be used in disease and pest control in case of Citrus black spot disease.…”
Section: Optimizing the Use Of Bio-digestersmentioning
confidence: 99%